2021
DOI: 10.1016/j.bpj.2021.02.027
|View full text |Cite
|
Sign up to set email alerts
|

DNA length tunes the fluidity of DNA-based condensates

Abstract: Living organisms typically store their genomic DNA in a condensed form. Mechanistically, DNA condensation can be driven by macromolecular crowding, multivalent cations, or positively charged proteins. At low DNA concentration, condensation triggers the conformational change of individual DNA molecules into a compacted state, with distinct morphologies. Above a critical DNA concentration, condensation goes along with phase separation into a DNA-dilute and a DNA-dense phase. The latter DNA-dense phase can have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 41 publications
12
32
0
Order By: Relevance
“…Similar results can be recapitulated using coarse-grained simulations that capture the overall trends of DNA compaction and phase separation propensity in the presence of a ligand. Taken all together, our observations support the original interpretation proposed by Post and Zimm (18) and are consistent with the idea that protein-dependent collapse of a single nucleic acid chain and the phase separation of mixtures of protein and nucleic acids are two distinct outcomes driven by the same set of molecular interactions (68, 82, 83).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results can be recapitulated using coarse-grained simulations that capture the overall trends of DNA compaction and phase separation propensity in the presence of a ligand. Taken all together, our observations support the original interpretation proposed by Post and Zimm (18) and are consistent with the idea that protein-dependent collapse of a single nucleic acid chain and the phase separation of mixtures of protein and nucleic acids are two distinct outcomes driven by the same set of molecular interactions (68, 82, 83).…”
Section: Discussionsupporting
confidence: 92%
“…One interpretation of these results reflects a model in which HP1a drives heterochromatin territories through bona fide liquid-liquid phase separation (7, 8, 21). Another is that the intrinsically multivalent nature HP1a and many other DNA binding proteins (such as TRF2) drives DNA compaction through distributed multivalent interactions which will inevitably also drive phase separation with sufficiently short nucleic acid molecules in vitro (68, 82, 88). Altering the degree of DNA compaction by modulating the same interactions that would also drive phase separation could allow for the rheostatic control of access to genomic loci.…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate how introducing one of these additional constraints, the very long length of chromosomes, would affect FRAP behavior we formed condensates composed of nucleosomal arrays with increasing length and found that photobleach recovery lessens at longer chromatin sizes (Figures 6A-6D). This length-dependent effect on condensate dynamics is general, as recently demonstrated with other biomolecular condensates in vitro (Keenen et al, 2021;Muzzopappa et al, 2021) or by fragmenting mitotic chromatin in cells (Schneider et al, 2021). This slowing of dynamics is driven by length-dependent steric occlusion of movement by neighboring molecules and increases in intermolecular contacts (Rubinstein and Colby, 2003).…”
Section: Bridging Fluid Condensates To Chromatin Dynamics In the Cellsupporting
confidence: 60%
“…It should be noted that the liquid chromatin droplets have high internal viscosity and are not particularly fluid [ 33 ]. Of note, it has recently been demonstrated that the material state of DNA-based condensates is sensitive to the DNA fragment length [ 65 ]. For both H1–DNA condensates and nucleosomal arrays, shorter (< 1 kb) DNAs formed liquid condensates while longer fragments formed more solid condensates.…”
Section: Phase Separation Of Chromatinmentioning
confidence: 99%